A PWL ASIC design for maximum throughput - Lifschitz, Omar D. (2013)
This paper presents the design of a digital architecture for a Simplicial piecewise linear (PWL) integrated circuit (IC). This design maximizes the IC throughput by using an enhanced pipeline architecture and taking advantage of the maximum memory device performance.